Fast Electrochemical Detection of Non-Desirable Aging in Bottled White Wine - Aguirre-Quintana, M; Aguirre-Quintana, M; Muena-Barria, J; Muena-Barria, J (Sociedad Chilena de Quimica, 2014)
Oenologists and wine exporters know that a serious problem is to determine the quality of wine after it travels to final market. In fact the last quality controls are made after the bottling and before the trip. Chile is an important exporter of wine and Asiatic markets are a common destination for this exportation, taking long times of traveling. If wine changes it quality due to different stressing situations during the trip, the final costumer will receive a low-quality beverage in spite of the high quality of the original wine. This fact can reduce the interest of the costumer to consume Chilean wine and diminishes the importations of this product. © 2014, Sociedad Chilena de Quimica. All right reserved.